ACQUISITION OF OWNERSHIP OF REAL ESTATE – CONSTITUTIONAL BALANCE BETWEEN THE INTERESTS OF AN ORIGINAL OWNER AND A BONA FIDE PURCHASER: ANALYSIS OF THE №3/4/550 JUDGMENT OF 17 OCTOBER 2017 OF THE CONSTITUTIONAL COURT OF GEORGIA (Law and world, 2017)
An unfettered transfer of property rights represents an inherent part of the constitutional right to property. It is widely conceived as a cornerstone of modern free market economy. The regulation of property alienation has evolved considerably from the ancient times till today, when registration of immovable property is an accepted practice. Despite various regulatory models exist worldwide, almost every state has moved to set up a centralised public registry in order to ensure recognition of ownership of real estate.